Exploring the research landscape in Malaysian higher education: a scopus-based analysis of publications from 2018 to 2022 / Suriana Che Daud, Haslinda Husaini and Nor Zaina Zaharah Mohd Arif - Che Daud, Suriana; Husaini, Haslinda; Mohd Arif, Nor Zaina Zaharah (Faculty of Information Management, 2023)
All Malaysian institutes of higher education have increased their research due to the relevance of publications. In this study, academic publications from the renowned SCOPUS database were examined. The study aimed to show: 1) The total number of publications from Malaysia in the Scopus database between 2018 and 2022, 2) To identify active authors in Malaysia in the Scopus database between 2018 and 2022. 3) To identify active institutions in the Scopus database between 2018 and 2022 and 4) To determine the subject covered by the published works in the Scopus database between 2018 and 2022. The study confined its scope to the publications produced between 2018 and 2022 by Malaysian authors published in Malaysia as well as abroad. The number of publications that most Malaysian universities put out is strongly influenced by factors like funding, training, resistance to change, and job satisfaction.